Les tombeaux des rois Zāgwē, Yemreḥanna Krestos et Lālibalā (XIIe-XVIe siècle), et leurs évolutions symboliques - Marie-Laure Derat (Afriques)
The tombs of two kings of the Zagwe dynasty, Yemrehanna Krestos and Lālibalā, are said to be located in churches that they founded. However this information does not figure in the first texts written about these Ethiopian saint-kings. The chronology of these texts and their production are presented; and the eras identified when new symbols emerged for authenticating the sepultures of saint-kings or modifying the perception of them. What processes led to identifying the location of these tombs and considering them to be the graves of saints, and no longer of kings? The tombs of these two kings have become places where pilgrims request these saints to intercede on their behalf.